Software Requirement Prioritization Prototype Using Analytical Hierarchical Process (AHP) - Rohani, Abu Bakar; Siti Syahidah, Mohd Kamal (2014)
Requirement prioritization process is recognized as one of the most important decision activities in Software Engineering decision support as it facilitates making the right decision in developing the right product. There are a lot of techniques in prioritizing requirements being researched and developed in order to accommodate the need of this process. However, most of the techniques requires high level of understanding and involve a number of complicated procedures to be adapted made the prioritization process usually being omitted in practices. In this study, a requirement prioritization tool (AHPrpt) is designed in order to accommodate the need of automated mechanism in prioritizing software requirements which implements Analytic Hierarchical Process (AHP) technique that provides pair-wise comparison for all comparison pairs in determining software requirements priority. Based on the analysis conducted, the correctness of AHPrpt is testified. The result obtained, verify AHPrpt is proven effective to be applied in requirement prioritization process.